SISTEM INFORMASI PEMBIMBINGAN SKRIPSI MENGGUNAKAN UML - Fauzi, Irfan -; Swanjaya, Daniel (Nusanatara of Engineering, 2014)
AbstractThesis is one of the guidingacademic activities that must be carried outby students after completing all the coursesthat must be taken during the learningprocess at the college undergraduate level.Applications guiding thesis is indispensablein controlling the process of coaching,facilitate consultation with a faculty mentorstudents without having to do a face to faceand evaluate the thesis topics for mentoringthe next period.Previous studies ever conductedThe study will be conducted using areference obtained from the literature aboutthe application online consultation formwith supporting documents draft partiallyThesis Thesis preparation and proceduresestablished by the University of PGRINusantara Kediri.The data collected consists of thedata that follows several students andfaculty mentor coaching Thesis anddocuments to be consulted students Thesis.While the report generated from thisresearch is on the evaluation of supervisionand monitoring activities.This activity is planned to becarried out for 6 months in accordance withthe guardianship of the stage of making athesis that includes spesification, design,coding, and testing.While the resulting outcome is anapplication that can be used by the system inthe process of thesis guidance and monitorimplementation of these activities as well asscientific articles on Informatics guidingÂ thesis using UML. The results of this studycan also be used as an example of teachingmaterials design Informatics analysis usingUML.Final results of the monitoringactivities of each student will be used as abasis for improving the guidance andreference in the preparation of the nextthesis, so that academic activities in theUniversity Studies Program InformationEngineering Nusantara Kediri PGRI canrun more intensive and successful.Keywords :Guiding Academic,Thesis, Software Engineering, UML